2007
DOI: 10.1152/ajpheart.00801.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voluntary wheel running on cardiac function and myosin heavy chain in chemically gonadectomized rats

Abstract: Reducing testosterone and estrogen levels with a luteinizing hormone-releasing hormone agonist such as Zoladex (i.e., chemical gonadectomy) is a common treatment for many prostate and breast cancer patients, respectively. There are reports of surgical gonadectomy inducing cardiac dysfunction, and exercise has been shown to be cardioprotective under these circumstances. Minimal research has been done investigating the effects of chemical gonadectomy and increased physical activity on cardiac function. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 88 publications
4
27
1
Order By: Relevance
“…The effects of hormone suppression (androgen deprivation therapy [ADT], oestrogen receptor antagonists and aromatase inhibitors) on cardiac function and exercise tolerance are also largely unknown. In preclinical work, ADT has been shown to impair cardiac function and cause higher β-myosin heavy chain distribution, 30 and the marked reduction in the bioactivity of oestrogen associated with aromatase inhibitor therapy theoretically raises concerns about the adverse cardiac effects of this therapy class.…”
Section: Mechanisms Of Impairmentmentioning
confidence: 99%
“…The effects of hormone suppression (androgen deprivation therapy [ADT], oestrogen receptor antagonists and aromatase inhibitors) on cardiac function and exercise tolerance are also largely unknown. In preclinical work, ADT has been shown to impair cardiac function and cause higher β-myosin heavy chain distribution, 30 and the marked reduction in the bioactivity of oestrogen associated with aromatase inhibitor therapy theoretically raises concerns about the adverse cardiac effects of this therapy class.…”
Section: Mechanisms Of Impairmentmentioning
confidence: 99%
“…Two other studies reported no sex differences in the effects of exercise on measures of escalation, binge responding, extinction responding, drug-primed reinstatement, and cue-induced reinstatement (Smith et al, 2011a,b). Gonadal hormones are known to influence both drug self-administration (Roberts et al, 1989; Feltenstein and See, 2007; Larson and Carroll, 2007; Mello et al, 2011) and wheel running (Hertrampf et al, 2006; Hydock et al, 2007), but it is not known whether gonadal hormones influence the effects of exercise on drug self-administration. Studies that experimentally manipulate the hormonal milieu via gonadectomy and receptor-specific antagonists will be necessary to characterize the role of sex-specific hormones in this relationship.…”
Section: Future Directions and Translational Implicationsmentioning
confidence: 99%
“…A growing body of evidence has also suggested that EX is a powerful intervention to mitigate ADT-related reductions of musculoskeletal and cardiorespiratory functions, but as yet, no study has evaluated the effects of EX on cardiac structure and function in patients receiving ADT [4] [6] [9] [11] [12]. In rodents, chemical orchiectomy has been associated with LV systolic dysfunction which was attenuated by EX [8]. Surprisingly, the present study failed to demonstrate significant changes in cardiac structure or function as measured by comprehensive echocardiography after 12 weeks of ST in patients receiving ADT as compared to controls, even though such intervention has previously been associated with substantial changes of echocardiographic variables in healthy men and men with hypertension or diabetes [14] [16] [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, ADT is associated with increased risk of cardiovascular disease (CVD) and risk factors such as adiposity, type 2 diabetes, increased circulating lipid levels and augmented central aortic stiffness, along with reduction of muscle strength and physical capacity [1]- [7]. Limited experimental evidence has also suggested that ADT can influence cardiac function and in rats ADT is associated with left ventricular (LV) dysfunction, which can be ameliorated by exercise training (EX) [8]. Exercise training level is inversely related to long term PCa survival and has been documented as a feasible, safe and effective means for improvement of fitness, body composition and quality of life in PCa patients undergoing ADT [4] [6] [9] [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%